Moving target detection with polarimetric distributed MIMO radar in heterogeneous clutter - Yan Xiang; Zhiwen Liu; Yulin Huang; Yougen Xu (The Journal of Engineering, 2019)
In this study, the authors consider the problem of moving target detection in the presence of heterogeneous clutter. The knowledge-aided method has been extended to derive the polarimetric multiple-input multiple-output (MIMO) radar detector. And the polarimetric clutter covariance matrix was modelled as a complex inverse Wishart distribution. More precisely, the clutter covariance matrices between different transmitter–receiver (Tx–Rx) pairs are assumed to follow the distribution which shares a prior clutter covariance matrix structure while with different values of the power levels. Under this assumption, the generalised likelihood ratio test (GLRT) approach has been adopted to develop the polarimetric knowledge-aided detector without secondary data. Numerical results are shown to illustrate the effectiveness of the polarimetric knowledge-aided GLRT detector in heterogeneous clutter.